2015
DOI: 10.1371/journal.pone.0134021
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Experience in the Diagnosis and Treatment of Infective Endocarditis

Abstract: AimsThe aim of this study was to compare the etiology, clinical course, selected diagnostic methods and efficacy of the treatment used in patients with infective endocarditis (IE) in the nineteen eighties and nineties.Material and MethodsThe study group comprised 300 patients with infective endocarditis hospitalized in the Institute of Cardiology in Warsaw in the following years: from 1982 to 1987 (150 patients: 75 successive patients with IE on the prosthetic valve and 75 successive patients with IE on the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Some infectious markers, such as CRP, erythrocyte sedimentation rate, and neutrophil, may contribute to early detection of the disease. 10 In this study, more than 50% Staphylococcus spp is the most common cause of IE, followed by Streptococci spp 13,14 .Staphylococcus spp associate IE has became increasingly common in most industrialized countries because of increased medical intervention 5 ; meanwhile Streptococci spp has became less 15,16 . the presence of S. aureus bacteremia should be considered a major criterion, regardless of whether the infection is nosocomially acquired or whether a removable source of infection is present 17 .…”
Section: Discussionmentioning
confidence: 75%
“…Some infectious markers, such as CRP, erythrocyte sedimentation rate, and neutrophil, may contribute to early detection of the disease. 10 In this study, more than 50% Staphylococcus spp is the most common cause of IE, followed by Streptococci spp 13,14 .Staphylococcus spp associate IE has became increasingly common in most industrialized countries because of increased medical intervention 5 ; meanwhile Streptococci spp has became less 15,16 . the presence of S. aureus bacteremia should be considered a major criterion, regardless of whether the infection is nosocomially acquired or whether a removable source of infection is present 17 .…”
Section: Discussionmentioning
confidence: 75%
“…Infective endocarditis with high morbidity and mortality is one of the most serious and destructive complication of valvular heart disease [2]. Congenital heart disease is a common cause of infective endocarditis [3], and studies have shown that the incidence can reach 10% to 14%, which is more common in VSD, congenital bicuspid aortic valve, patent ductus arteriosus (PDA), and tetralogy of Fallot.…”
Section: Discussionmentioning
confidence: 99%
“…Individual studies revealed that the clinical profile of IE has changed over the past few decades [4,5]. Presented studies show several factors evolving over time, including risk factors, etiology and high prevalence of IE cases caused by nosocomial infections [6,7]. Data on the IE in Poland are very limited.…”
Section: Introductionmentioning
confidence: 99%